2013
DOI: 10.3177/jnsv.59.289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 48-h Food Deprivation on the Expressions of Myosin Heavy-Chain Isoforms and Fiber Type-Related Factors in Rats

Abstract: The primary aim of this study was to examine the effects of 48-h food deprivation on rat skeletal muscle fiber type, according to myosin heavy-chain (MyHC) isoform composition and some metabolism-related factors in both slow-type dominant and fast-type dominant muscle tissues. Male Wistar rats (7 wk old) were treated with 48-h food deprivation or ad libitum feeding as control. After the treatment, the soleus muscle (slow-type dominant) and the extensor digitorum longus (EDL, fast-type dominant) were excised. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Thus, initial conditions may have been similar to the soybean oil-fed group. Previously, we reported the effects of 48-h food deprivation on muscle fiber type properties [ 50 ].. In that study, rats of the same strain, age, breeder, and commercial diet (CRF-1) were used and MyHC composition of the control group was very similar to this experiment in both EDL and soleus muscle.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, initial conditions may have been similar to the soybean oil-fed group. Previously, we reported the effects of 48-h food deprivation on muscle fiber type properties [ 50 ].. In that study, rats of the same strain, age, breeder, and commercial diet (CRF-1) were used and MyHC composition of the control group was very similar to this experiment in both EDL and soleus muscle.…”
Section: Discussionmentioning
confidence: 95%
“…Fasting, however, should have little effect on the expression of type I MyHC isoforms ( Mizunoya et al , 2013 ). Instead, the decreased expression by October ice bears indicates that summer atrophy was also at least partially caused by reduced activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition the glycolytic fibers were selectively decreased in the cross sectional area lead to a proportional increase in the area of oxidative fibers in bovine muscle (Greenwood et al, 2009). Muscle phenotype also changed according to the dietary challenges, It has been reported that dietary deprivation for 48 hours upregulates the expression of fast myosin heavy chain 2b mRNA with no change in fiber type composition for EDL and soleus muscles in rat (Mizunoya et al, 2013b) However 4 weeks fatty diet administration induced reduction in the fast MHC2b and improved the oxidative metabolism in the EDL of rat (Matsakas et al, 2013;Mizunoya et al, 2013a). Previously, it was shown that fasting induces muscle proteolysis via glucocorticoid activation (Wing and Goldberg, 1993) as well as causing an increase in the ATP-dependent proteolysis and upregulation of ubiquitin conjugates and polyubiquitins in rat skeletal muscle (Medina et al, 1991).…”
Section: Introductionmentioning
confidence: 99%